PHARMACOLOGICAL IMPORTANCE OF MORINGA CONCANENSIS NIMMO LEAF: AN OVERVIEW - SINGH, AMERENDRA; MISHRA, JAI NARAYAN; SINGH, SANTOSH KUMAR (Asian Journal of Pharmaceutical and Clinical Research, 2019)
In the current years, the use of traditional medicine is increasing and gaining popularity. The extracts of Moringa concanensis Nimmo leaves have reported many medicinal uses. In the previous few decades, a massive quantity of scientific facts concerning plants, crude extracts, and quite a number supplies from plant life as medicinal dealers has come to light. M. concanensis is a plant whose components are oftentimes used in the medicinal treatments. There are good sized anecdotal facts about the organic undertaking of M. concanensis which includes anticancerous, antibacterial, antifungal, analgesic, and anti-inflammatory type of activities. The leaves of M. concanensis had been located to contain a higher quantity of triterpenoids and flavonoids. The existing assessment includes the phytochemical, ethnopharmacological, and pharmacological reviews of M. concanensis. The future scope of the plant has been emphasized with a view to isolate bioactive moieties which should be used for multifarious biological activities.